DEVELOPMENT OF THE ADAPTED GENE POOL FOR ALTERNATIVE WAY OF LIVING OF SOFT WHEAT - V. A. Filobok; Е. A. Guenkova; L. А. Bespalova; V. A. Koshkin; E. K. Potokina (Зерновое хозяйство России, 2018)
The agricultural crops of dvuruchki (spring-winter wheat) possess advantages among winter and spring wheat due to genetically substantiated high adaptability that makes them the most popular crops in the production. The first variety of dvuruchka ‘Lastochka’, developed in 2005, possessed insufficient winter-frost tolerance and could freeze during hard winters. The variety ‘Afina’, developed in 2009, is more frost resistant, with high content of protein and tolerant to fuzariosis. Winter-frost resistance of the variety ‘Pallada’ is nearly the same as of the middle frost resistant variety ‘Bezostaya 1’. Besides, the variety ‘Pallada’ with a yellowish bread crumb due to the gene Y, is a carrier of the gene of leaf rust resistance Lr 19, closely connected with the gene of stem rust Sr 25, efficient against Ug 99, received from Ag. elongatum. When we improved the developed technology of the breeding process of the varieties with alternative way of living, made multiple artificial selections together with a natural selection under changeable effect of the factors which form the systems of adaptability of winter, spring and facultative ways of living, we created the variety ‘Anka’. The variety ‘Anka’ has been developed with the method of ecologic selection. Examining the responsiveness to day length (photosensitivity) and the demands in vernalization in KRIA (Krasnodar) the initial line of the variety ‘Anka’ showed itself as a reliable natural dvuruchka, i.e. it permanently produced heads at spring sowing and overwintered well (as the winter wheat variety ‘Bezostaya 1’) being artificially frozen in the fridge boxes and then tested on winter-frost tolerance on the shelves. The study of the line in ARRIR named after N.I. Vavilov (St.Petersburg) confirmed its weak sensitivity to vernalization and high sensitivity to photoperiod. Molecular testing of the alleles of the genes Vrn and Ppd showed the presence of the recessive allele of the gene Ppd-D1 responsible for high photosensitivity and found recessive alleles of the genes Vrn-А1, Vrn-В1 and a dominant allele of the gene Vrn-D1 responsible for reducing the need of vernalization. The variety ‘Anka’ is of middle-height, middle-maturing, heat tolerant and drought resistant. According to its grain productivity is possesses advantages before the standard varieties. High content of protein (up to 18,5%) and gluten (up to 35%) gives high nutrition of bread, made from flour of the variety.